Peran Interaksi Sosial Terhadap Pengembangan Bahasa Anak Usia Dini - Sofiah Sofiah; Nur Aliyah (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The development of Indonesian in children is important because communication and social interaction are important aspects of their development. Through speaking, they can communicate and interact with other people. One way to encourage language development in early childhood is through social interaction. This research aims to explore how social interaction influences language development in early childhood. We involved 10 students from Istiqomah Kindergarten, including 3 who tend to be introverted and have difficulty interacting with their friends. We use observation methods, interviews with teachers, and observations of students over a certain period. The research results show that social interaction has a significant role in improving language skills in early childhood. The development of Indonesian in children is important because communication and social interaction are important aspects of their development. Through speaking, they can communicate and interact with other people. One way to encourage language development in early childhood is through social interaction. This research aims to explore how social interaction influences language development in early childhood. The research results show that social interaction has a significant role in improving language skills in early childhood.